Determinants of Exporting Firm in Indonesian Food Processing Sector - Rifin, Amzul (Universitas Prasetiya Mulya, 2017)
Firm size, foreign networks and location has been analyzed as the factors in differentiating between exporting and nonexporting firms. The objective of this study is to analyze factors which made the firms export on the case of food processing sector in Indonesia. The data utilized is the Industry Survey in 2013 by the Statistics Indonesia. The results indicate that foreign networks, represent by foreign shares and imported input, and location are affecting firm to export. Meanwhile from four variables of firm size only one variable has significant effect (production worker expenditure). From these variables it can be inferred that linking with foreign side in the form of share or inputs will induce firm to export.